2011
DOI: 10.1080/00224499.2010.494257
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Sexual Risk Behavior among Croatian College Students, 1998-2008

Abstract: A substantial increase in religious identification has been observed in most European post-communist countries. As religiosity has been associated with sexually transmitted infection (STI) and HIV vulnerability among young people, this article examined the impact of religious upbringing and personal religiosity (religiousness) on sexual risks among University of Zagreb first-year undergraduate students, using data collected in 1998, 2003, and 2008. Female participants who reported strict religious upbringing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 33 publications
(35 reference statements)
2
23
1
1
Order By: Relevance
“…Similar study showed that the effect of religiosity on STI reduction and HIV‐related risk‐taking was modest, especially among men (Stulhofer et al. ). No recent data about this are available for Bosnia and Herzegovina, making our references concerning Bosnia limited.…”
Section: Discussionmentioning
confidence: 83%
“…Similar study showed that the effect of religiosity on STI reduction and HIV‐related risk‐taking was modest, especially among men (Stulhofer et al. ). No recent data about this are available for Bosnia and Herzegovina, making our references concerning Bosnia limited.…”
Section: Discussionmentioning
confidence: 83%
“…Although 31.6% of undergraduates were currently in a heterosexual relationship, 19.6% reported being sexually active and having sexual intercourse. In comparison, in studies conducted among Western college students, that figure ranged from 69% to 85% (Adefuye et al ., ; Stulhofer et al ., ); Chinese undergraduates have relatively less sexual experience. While social desirability effects might have led to underreporting of sensitive topics of sexual behaviors (Chi et al ., ), this study included a social desirability scale and found that undergraduates in this study gave non‐social desirability responses, rather than socially‐desirable responses.…”
Section: Discussionmentioning
confidence: 99%
“…Além de a religiosidade e a frequência de participação aos cultos e celebrações do próprio jovem terem impacto sobre sua iniciação sexual, outras variáveis estiveram presentes nos estudos, como a religiosidade da família e da comunidade -quanto mais religiosas, menores as chances de o jovem ter se engajado em atividades sexuais ou possuir opiniões mais liberais (SCHEEPERS et al, 2002;BURDETTE;HILL, 2009;STULHOFER, 2011). Segundo os autores, isso é sinal de que adolescentes podem ser influenciados pela comunidade onde vivem, mas também que os custos psicológicos de engajar em atividades sexuais em comunidades muito religiosas podem ser altos.…”
Section: Mundounclassified